MENINGKATKAN HASIL BELAJAR DENGAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS - Yayah Afiah (Perspektif Ilmu Pendidikan, 2012)
The Grade X-7 students’ understanding of writing argumentative paragraph is still low as the students do not listen to the teacher’s explaination attentively, do not care the use of correct spelling, diction, effective sentence, paragraph coherence, and integerated passage. To overcome these problems, the researcher performed classroom action research aiming at imroving the students’ competence in writing argumentative paragraph. The research was conducted in Grade X-7 of State High School, No. 7, in Jakarta as from January through February 2012 employing Teams Games Tournaments (TGT) Model. After the second cycle of the research, the students’ learning achievement indicated the average of 72 with the learning mastery of 75 % showing the significant improvement. It was concluded that TGT Model can be used to improve the students’ learning achievement in argumentative paragraph writing. Besides, the research recommended a set of steps how to use the model.